A 450-year lacustrine record of recurrent seismic activities around the Fuyun fault, Altay Mountains, Northwest China. (30th August 2020) - Fan, Jiawei; Jiang, Hanchao; Shi, Wei; Guo, Qiaoqiao; Zhang, Siqi; Wei, Xiaotong; Xu, Hongyan; Zhong, Ning; Huang, Shuaitang; Chang, Xiangde; Xiao, Jule
Abstract: Seismic hazards and risks around an individual fault can be assessed from complementary paleoseismic data. A high-resolution sediment core recovered from the Yileimu Lake revealed 11 potential paleoearthquakes around the Fuyun fault in northern Xinjiang. Among them, three events recorded by ductile deformation and turbidites or coseismic subsidence were possibly correlated with M s  ≥ 7.0 earthquakes, and the others characterized by turbidites or coarse deposits were likely related to M s  ≥ 5.8 or M s  ≥ 5.5 earthquakes. Shaking intensities of 8.60 and 5.51 MMI were required to cause extensive landslides and turbidites, respectively; while 6.89, 6.35 and 5.34 MMI were likely to be required to cause coseismic subsidence, ductile deformation and coarse deposits related to landscape shattering in the catchment area, respectively. Absolute radiocarbon dating and historical earthquake-event markers disclosed a recurrence interval of 20–60 years for M s  ≥ 5.5 earthquakes, and a potential interval of 100 years for M s  ≥ 7.0 earthquakes during the last 450 years. A seismic quiescence of 89 years since the 1931/08/11 M s 8.0 Fuyun earthquake might have significantly increased the potential of a strong earthquake related to the fault in the near future. Highlights: Lake sediments recorded 11 potential paleoearthquakes around the Fuyun fault. Intensities and magnitudes for distinct sedimentary events were distinguished. Recurrence intervals for earthquakes with different magnitudes were proposed.